The Potential of Tanjung Sawit Village as the Best Village in Riau Province - Batubara, Ummi Mardhiah; Bernadi, Haryo Jati; Fitri, Sri Afifah; Syahputri, Rara Vania; Situmorang, Novita; Kartini, Kartini; Anggelina, Anggelina; Arfan, Muhammad; Delvi, Ayu; Azahra, Mutiara Mindy (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This program in Tanjung Sawit Village aims to enhance village potential and empower the community through academic involvement and technological support. It utilizes information technology for effective promotion. Method: By employing participatory research methods involving academics and locals, data is gathered through surveys, interviews, and observations and then analyzed for insights. Practical Applications: The program yields tangible results, including a village profile, online promotion tools, and improved governance. It fosters community skills and empowerment, exemplified by the formation of oil palm farming groups. Conclusion: The collaborative effort demonstrates the value of academia-community partnerships in rural development. Leveraging technology and community engagement can address local challenges and promote inclusive growth, serving as a model for broader development strategies.